2013
DOI: 10.1111/jnu.12000
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, Legal, and Social Issues in the Translation of Genomics Into Health Care

Abstract: Purpose: The rapid continuous feed of new information from scientific discoveries related to the human genome makes translation and incorporation of information into the clinical setting difficult and creates ethical, legal, and social challenges for providers. This article overviews some of the legal and ethical foundations that guide our response to current complex issues in health care associated with the impact of scientific discoveries related to the human genome. Organizing Construct: Overlapping ethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…It is imperative that both the patient and provider understand and comprehend issues such as human rights, harm and benefit, transparency, and informed consent. 38 Differences across racial/ethnic groups in understanding the risks and benefits of genomic medicine could result in disparities of care related to use, rather than access, to genomic medicine and personalized care.…”
Section: Challengesmentioning
confidence: 99%
“…It is imperative that both the patient and provider understand and comprehend issues such as human rights, harm and benefit, transparency, and informed consent. 38 Differences across racial/ethnic groups in understanding the risks and benefits of genomic medicine could result in disparities of care related to use, rather than access, to genomic medicine and personalized care.…”
Section: Challengesmentioning
confidence: 99%
“…It has been suggested that a broader understanding of how genomics relates to chronic conditions could help clinicians better assess risk and plan management of patients (Taylor et al, 2013). Conversely, it is obligatory that providers understand the community knowledge so that care can be comprehensive and culturally sensitive (Badzek et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The evidence base on epigenetics and genomic literacy (as defined above) is developing (Badzek, Henaghan, Turner, & Monsen, 2013; Calzone, Jenkins, Nicol, et al, 2013; Conley et al, 2013; Roberts, Dolinoy, & Tarini, 2014). Ensuring the public has access to the knowledge and skills needed to keep up with the technical intricacies of “genetic and genomic information” has been a focus of The American Public Health Association, Health People 2020, and the Institute of Medicine.…”
mentioning
confidence: 99%
“…[7] The influence on practice is swiftly advancing and with emerging ethical, legal and social issues, including confidentiality, therapeutic decision-making capacity, informed consent, genetic screening and testing, risk assessment, prevention, diagnosis, prognosis and research are necessary to guarantee the delivery of appropriate and unprejudiced health care for all. [8,9] The clinical significance requires a broad familiarity of genetic-genomic concepts, staying informed of new genomic technology and being able to incorporate this information through informed comprehensive nursing practice. [2] Expanding on the core proficiencies, prominent national and international nursing organizations established guidelines for the integration of contemporary G-G knowledge related to nursing, instituting a foundational knowledge base as a basic requirement in nursing education.…”
Section: Literature Reviewmentioning
confidence: 99%